การเปรียบเทียบการใช้โปรแกรมสำเร็จรูปทางสถิติ SPSS, MINITAB, PSPP และ R สำหรับสถิติศาสตร์ไม่อิงพารามิเตอร์ - งามสุข ธนัชพร; นาไชย พัชราภา; สินสมบูรณ์ทอง สายชล (Thai Journal of Science and Technology, 2021)
The objective of this research was to compare four computer statistics program packages – SPSS, MINITAB, PSPP, and R – in terms of test statistics and p-value from nonparametric statistical analyses. The nonparametric analyses performed were the following: one sample test, two independent sample tests, two related sample tests, a k-independent sample test, and a k-related sample test. For each test in the nonparametric analyses of three examples of problems. Our findings may directly benefit future developers of comprehensive guidelines for using these computer statistics programs. The results revealed that, for one sample test, the R program was the most suitable for use. For two independent sample and two related sample tests, the SPSS program was the most suitable for use. For the k-independent sample test, the R program was the most suitable for use. For the k-related sample test, SPSS and R programs were the most suitable for use. SPSS and R programs provided the most ideal for service to the nonparametric.